2020
DOI: 10.1096/fj.201902976r
|View full text |Cite
|
Sign up to set email alerts
|

Three months of bed rest induce a residual transcriptomic signature resilient to resistance exercise countermeasures

Abstract: This study explored the muscle genome‐wide response to long‐term unloading (84‐day bed rest) in 21 men. We hypothesized that a part of the bed rest‐induced gene expression signature would be resilient to a concurrent flywheel resistance exercise (RE) countermeasure. Using DNA microarray technology analyzing 35 345 gene‐level probe‐sets, we identified 335 annotated probe‐sets that were downregulated, and 315 that were upregulated after bed rest (P < .01). Besides a predictable differential expression of genes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 54 publications
5
37
0
Order By: Relevance
“…Corroborating previous spaceflight studies in worms (Adenle et al, 2009; and rodents (Blaber et al, 2017;Kuznetsov et al, 2019), across spaceflight missions we found consistently upregulated genes associated with altered rates of cell cycle, DNA modification, and actin cytoskeleton/ Genes enriched for ubiquitin-dependent protein degradation were also consistently upregulated by spaceflight conditions, consistent with observations in space-flown rodent liver (Blaber et al, 2017) and skeletal muscle tissue (Nikawa et al, 2004), and human skeletal muscle using ground-based spaceflight analogs (bedrest/immobilization; Fernandez-Gonzalo et al, 2020;Reich et al, 2010). Although counter to earlier reports of unaltered bulk protein degradation in space-flown C. elegans (Etheridge et al, 2011), low-level increases in ubiquitin-proteasome mediated breakdown could be protective against cytotoxic increases in protein aggregates, as occurs during simulated microgravity (Aleshcheva et al, 2013) and animal aging (Melentijevic et al, 2017), a pathophysiological analog of microgravity.…”
Section: Reproducible Gene Signatures Of Micro-and Hypergravity Adaptsupporting
confidence: 89%
“…Corroborating previous spaceflight studies in worms (Adenle et al, 2009; and rodents (Blaber et al, 2017;Kuznetsov et al, 2019), across spaceflight missions we found consistently upregulated genes associated with altered rates of cell cycle, DNA modification, and actin cytoskeleton/ Genes enriched for ubiquitin-dependent protein degradation were also consistently upregulated by spaceflight conditions, consistent with observations in space-flown rodent liver (Blaber et al, 2017) and skeletal muscle tissue (Nikawa et al, 2004), and human skeletal muscle using ground-based spaceflight analogs (bedrest/immobilization; Fernandez-Gonzalo et al, 2020;Reich et al, 2010). Although counter to earlier reports of unaltered bulk protein degradation in space-flown C. elegans (Etheridge et al, 2011), low-level increases in ubiquitin-proteasome mediated breakdown could be protective against cytotoxic increases in protein aggregates, as occurs during simulated microgravity (Aleshcheva et al, 2013) and animal aging (Melentijevic et al, 2017), a pathophysiological analog of microgravity.…”
Section: Reproducible Gene Signatures Of Micro-and Hypergravity Adaptsupporting
confidence: 89%
“…Head-down bed rest leads to changes in circadian/diel rhythms of physiological, metabolic and locomotion [39][40][41][42][43]. At the molecular level, upregulation of genes involved in circadian rhythm was found during and after 84 days of head-down tilt bed rest [12].…”
Section: Discussionmentioning
confidence: 98%
“…It has also been demonstrated that the circadian rhythms of diverse organisms display signi cant changes in space [6][7][8][9][10]. Among different space environmental factors, the effects of microgravity and lighting conditions on circadian rhythms have been extensively investigated [9,[11][12][13][14][15]. However, the potential effects of other factors, such as noise and low atmospheric pressure, on circadian rhythms remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, these skeletal muscle facets are dysregulated features in aging and following disuse and recovery in humans and rodents [ 6 , 10 , 31 , 32 , 33 , 34 ]. Moreover, PGC-1α expression has been observed to be lower with advanced age [ 35 , 36 , 37 , 38 , 39 ], during atrophy-inducing conditions [ 24 ], during disuse [ 40 , 41 , 42 , 43 ], and in recovery from disuse [ 44 , 45 ]. Interestingly, PGC-1α overexpression in rodent muscle can prevent disuse-induced atrophy [ 24 , 46 , 47 ].…”
Section: Role Of Pgc-1α In Skeletal Muscle Aging Atrophy and Recomentioning
confidence: 99%